2016
DOI: 10.1111/sms.12648
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic movement frequency is associated with muscle typology in athletes

Abstract: There is a continuing research interest in the muscle fiber type composition (MFTC) of athletes. Recently, muscle carnosine quantification by proton magnetic resonance spectroscopy ( H-MRS) was developed as a new non-invasive method to estimate MFTC. This cross-sectional study aims to better understand estimated MFTC in relation to (a) different disciplines within one sport; (b) cyclic sport exercise characteristics; (c) within-athlete variability; and (d) athlete level. A total of 111 elite athletes (74 runne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 30 publications
(48 reference statements)
4
28
1
1
Order By: Relevance
“…Additional research is needed to better understand the physiological mechanisms and finer-scale anthropometric variables underlying the sprint/endurance performance trade-off in human swimmers. In a confirmation of earlier findings in runners [30], one recent study showed, for example, that the muscle fibre-type composition of athletes varied based on the length of their event in swimmers, in addition to runners and other athletes [31]. Notably, within each swimming and running event, the mean difference between men and women competitors' BMI corresponded nearly exactly with the mean difference in race speed (both are 11% different; electronic supplementary material, table S1).…”
Section: Discussionsupporting
confidence: 70%
“…Additional research is needed to better understand the physiological mechanisms and finer-scale anthropometric variables underlying the sprint/endurance performance trade-off in human swimmers. In a confirmation of earlier findings in runners [30], one recent study showed, for example, that the muscle fibre-type composition of athletes varied based on the length of their event in swimmers, in addition to runners and other athletes [31]. Notably, within each swimming and running event, the mean difference between men and women competitors' BMI corresponded nearly exactly with the mean difference in race speed (both are 11% different; electronic supplementary material, table S1).…”
Section: Discussionsupporting
confidence: 70%
“…Given the fact that high proportions of type-I fibers are suggested to display greater mechanical efficiency at common movement frequencies (i.e., 1–2Hz, e.g., cycling between 60 and 120 rpm) that are close to the type-I fiber's peak efficiency velocity (He et al, 2000 ; Joyner and Coyle, 2008 ), a higher percentage of type-I fibers would relate to a higher gross efficiency (Coyle et al, 1992 ; Horowitz et al, 1994 ), and therefore contributes to a higher endurance performance (Horowitz et al, 1994 ). Nowadays, non-invasive techniques such as 1 H-MRS measurements of muscle carnosine content are also used to estimate type-I and II muscle typology, thereby confirming prior muscle biopsy-based findings across athletes (Baguet et al, 2011 ; Bex et al, 2017 ; Lievens et al, 2020 , 2021 ).…”
Section: The Overlooked Underlying Physiology: Skeletal Muscle Determinants Of Endurance Performancementioning
confidence: 77%
“…MHC II also has a superior ability to hypertrophy (Billeter et al, 2003). Further characteristics of MHC II muscle include larger baseline muscle carnosine content (Parkhouse et al, 1985;Baguet et al, 2011) that have been related to frequency of movement (i.e., more MHC II, higher frequency of movement) (Bex et al, 2017); and enhanced muscle buffering. In addition, greater creatine content is also found at rest in MHC II muscle, which supports more anaerobic based exercise (Tesch et al, 1989).…”
Section: Selection Of Appropriate Intervention-are All Stimulus Created Equal?mentioning
confidence: 99%